Degeneration of Character, Aesthetics of Origin, and Augmented Absence in Posthuman Cinema - Savaş Keskin (Filmvisio)
This article attempts to perform a sociological, anthropological, and especially philosophical analysis, critique, and constructive aesthetics of the artificial intelligence-assisted performer/character that has emerged in the cinematic universe of the post-human age or post-anthropocene, often referred to as posthumanism. Computers, which have evolved from merely assisting humans to becoming ‘social performers,’ are recontextualized in this article as ‘cinematic performers’ thanks to their artificial intelligence, and are evaluated solely based on their structural presence. The concept of the performer is used as a conceptual measure against the inequality effect of the masculine and gendered use of the term ‘actor’ in cinema. Since the transition from conceptualizing Computers as Social Actors/ Performers (CASA) to conceptualizing Computers as Cinematic Actors/Performers (CACA) cannot be limited to the McDonaldization approach—which includes the technomaly of an artificial intelligence that completely replaces humans—, the post-McDonaldization approach, which finds the integration of human-artificial intelligence more plausible, will prevail. This integrated hybridization results in a new mode of existence characterized as ‘augmentedness,’ an ‘excess,’ ‘expansion,’ and ‘quantitative concentration’ observable in all codes of reality, human and cinematic narrative. This intriguing entity allows us to discuss the problem of degeneration, the trans-aesthetics of origin that becomes inevitable with the marginalization of the aesthetics of origin, and the absolute absence and omnipresence of absence behind the claim of augmented or extreme phenomena to represent everything. What does cinema mean as the product of a character created as codes (computer code) in a trans-image form that transcends characters created as modus in the form of an image? Discussing this question is more than reducing the future of cinema to the present. Understanding the new performative identity of the character will help generate points of critical resistance to be added to the linear of expectations and hopes.